(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The study aimed to investigate the impact of social media marketing on purchase intention among consumers in Kosovo as a transition economy. The survey research has been conducted with a sample of 334 respondents in Kosovo, using an online survey tool for response collection. Structural equation modeling was used for assessing the proposed theoretical model. The bootstrapping technique was used to test the hypotheses and the mediating effects of brand awareness and brand engagement. The findings revealed a positive indirect impact of social media marketing on purchase intention and a full mediating effect of brand awareness and brand engagement in the relationship between social media marketing and purchase intention. The contribution of this study is that it provides insights into the impact of social media marketing on brand awareness, brand engagement, and purchase intention in transition economies. Moreover, it highlights the impact of social media marketing on enhancing brand awareness, brand engagement, and purchase intention in emerging economies in general and in particular in Kosovo. On a practical level, research results provide customers’ insights relevant for designing effective social media marketing strategies for their potential prospects in transition economies.